2020
DOI: 10.1007/s12649-020-01253-5
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Role of Experimental Olefin-Maleic-Anhydride Copolymer Based Compatibilizing Additives in Blends of Waste PET Bottles and Polyamide

Abstract: Over the past 50 years demand for plastics drastically increased worldwide resulting in plastic wastes causing serious environmental problems. The main market sector of European plastics industry is the packaging industry most of which are polyolefins and poly(ethylene-terephtalate). In the EU, 29.1 million tonnes of plastic waste were collected in 2018, of which 32.5% was recycled, 42.6% was recovered for energy, and 24.9% was landfilled (Plastics-the Facts, 2019). Although landfilling of collected waste in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Maleic-anhydride-grafted polypropylenes are widely used to compatibilize glass-fiber-reinforced polypropylene composites as well as thermoplastic blends and (partially) biobased composites. , With increasing demand for high-end applications and the global strive toward full recyclability of polyolefins, compatibilization of such materials has regained the interest of both academia , and industry . Although several synthetic functionalization pathways are well-studied, , the subsequent effect on the bulk crystallization of isotactic polypropylene (iPP) is still underexposed; under quiescent conditions, Cho et al observed a slight increase in the crystallization temperature and thus in the non-isothermal crystallization kinetics above a critical grafting content .…”
Section: Introductionmentioning
confidence: 99%
“…Maleic-anhydride-grafted polypropylenes are widely used to compatibilize glass-fiber-reinforced polypropylene composites as well as thermoplastic blends and (partially) biobased composites. , With increasing demand for high-end applications and the global strive toward full recyclability of polyolefins, compatibilization of such materials has regained the interest of both academia , and industry . Although several synthetic functionalization pathways are well-studied, , the subsequent effect on the bulk crystallization of isotactic polypropylene (iPP) is still underexposed; under quiescent conditions, Cho et al observed a slight increase in the crystallization temperature and thus in the non-isothermal crystallization kinetics above a critical grafting content .…”
Section: Introductionmentioning
confidence: 99%
“…In the additives containing functionalized MA, the acid number and the MA content/ratio do not offer sufficient information to select the appropriate compatibilizing additive for a given composite material based on its chemical structure, which would be more advantageous in many cases. The experimental olefin-maleic anhydride copolymer based additive, synthesized at the University of Pannonia, in which the anhydride ring was functionalized with various compounds, proved to be more advantageous in numerous composite system compared to the commercial MA-grafted polymer types [ [35] , [36] , [37] , [38] , [39] , [40] ]. The synthesis of olefin-maleic anhydride copolymer-based additives allows to applying the additive with the proper chemical structure in the various composite systems, since the structure of the additive can be tailored to the structure and polarity of the polymer and/or rubber components.…”
Section: Introductionmentioning
confidence: 99%